Distribution and isotopic compositions of n-alkanes and n-alkenes in the cryoconites from the Tibetan Plateau glaciers - Quanlian Li; Shichang Kang; Shijin Wang; Ninglian Wang; Xiaobo Wu; Wasim Sajjad; Huan Yang; Yao Li; Jingquan Wu (Journal of Glaciology)
In the current study, cryoconite samples were collected from six glaciers on the Tibetan Plateau to analyze n-alkanes and n-alkenes. The findings revealed that the concentrations of n-alkanes and n-alkenes varied from 40.1 to 496.1 μg g−1 and from 4.6 to 13.8 μg g−1, respectively. The carbon preference index of the long-chain n-alkanes ranged from 3.3 to 8.4, and the average chain length ranged from 28.7 to 29.3. Moreover, the δ13C of the n-alkanes in cryoconites were within the range of C3 plants, demonstrating that the n-alkanes in cryoconites were only derived from vascular plants. However, the δDmean were more negative than that of C3 plants, which could be caused by dry and humid conditions of glaciers. Unlike n-alkanes, n-alkenes ranged from C17:1 to C30:1 and showed a weak even-over-odd carbon number preference in the Dongkemadi, Yuzhufeng, Laohugou and Tianshan glacier, but a weak odd carbon preference in the Qiyi glacier. The n-alkenes in the YL Snow Mountains showed an obvious odd-over-even carbon number predominance from C17:1 to C22:1 with Cmax at C19:1, and the even-over-odd carbon number preference from C23:1 to C30:1 with Cmax at C28:1. This demonstrated that the n-alkenes of cryoconites may be mainly derived from in situ production in glaciers.